The need of subsidy for the implementation of photovoltaic solar energy as supporting of decentralized electrical power generation in Brazil - Silveira, Jose Luz [UNESP]; Tuna, Celso Eduardo [UNESP]; Lamas, Wendell de Queiroz [UNESP] (Elsevier, 2013)
The growing demand for electrical power and the limited capital invested to provide this power is forcing countries like Brazil to search for new alternatives for electrical power generation. The purpose of this paper is to present a technical and economic study on a 15 kW solar plant installed in an isolated community, highlighting the importance of the need for financial subsidy from the government. It evaluates the importance of parameters such as the annual interest rate, specific investment, the marginal cost of expanding the electrical power supply and the government subsidy on amortization time of capital invested. © 2012 Elsevier Ltd All rights reserved.
Keywords: Decentralized generation; Economic analysis; Photovoltaic panels; Renewable energy; Solar energy; Economic study; Electrical power; Electrical power generation; Electrical power supply; Financial subsidies; Government subsidies; Growing demand; Interest rates; Isolated community; Marginal costs; Photovoltaic solar energy; Renewable energies; Solar plant; Specific investment; Depreciation; Photovoltaic cells